Culturally Responsive Project-Based Learning: Enhancing Academic Writing Skills of Cambodian Students in Indonesia - Rasyimah Rasyimah; Muhammad Iqbal; Novi Diana; Ristawati Ristawati; Hasniyati Hasniyati (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
Academic writing skills in English are crucial competencies for foreign students, including Cambodian students at Malikussaleh University, but challenges such as linguistic differences and a lack of contextual practice often hinder their achievement. Although Project-Based Learning (PBL) is considered an effective approach, research on its implementation for small groups of foreign students in Indonesia is still limited, especially for the Southeast Asian cultural context. This study aims to analyze the effectiveness of PBL in improving the academic writing skills of Cambodian students while exploring their response to the method. Using a mixed-methods design with a one-group pretest-posttest approach, the study involved 7 Cambodian students who took PBL-based English courses for one semester. Results showed a significant improvement (p < 0.05) in the organization of ideas, grammar, and vocabulary, alongside positive feedback on increased confidence and collaboration. These findings prove that PBL can be adapted to small classes of foreign students, although modifications are needed to address constraints like ability heterogeneity. This research offers a contextual PBL model for Cambodian learners in Indonesia and contributes to the literature on PBL in specific EFL settings.